Social Problems in The Process of Land-Water Reform in Uzbekistan - Normurodovna , Hamroeva Nodira (Excellencia: International Multi-disciplinary Journal of Education (2994-9521), 2024)
In this article, in the first years of the new economic policy in the Autonomous Republic of Turkestan, the number of poor peasants among the rural population decreased somewhat. As mentioned above, market relations had a positive effect on this, and on the other hand, the land reform of 1921-22 had a positive effect. During these years, the weight of middle-class farmers increased significantly.